REGRESI DATA PANEL: PROFITABILITAS, PERTUMBUHAN AKTIVA, DAN SOLVABILITAS TERHADAP KEBIJAKAN DIVIDEN - Pangestuti, Dewi Cahyani (Economic Faculty, Attahiriyah Islamic University, 2020)
Purpose- The study was conducted with the aim to determine the effect of profitability, asset growth, and leverage on dividend policy.Design/methodology/approach- The objects in this study are companies included in the calculation of the Jakarta Islamic Index (JII) in a row during the study year, from 2014 to 2018. There were 14 companies selected as research samples, sample selection using purposive sampling method containing certain criteria in accordance with the needs of the research conducted. Data analysis was performed with the help of Microsoft Excel 2010 software and E-views 10. Panel data regression analysis was carried out in this study because it saw data types in the form of cross-sections and time series with a significance level of 5%.Findings- The test results obtained (1) Profitability explained by Return On Equity has a significant effect with a positive direction on dividend policy, (2) Asset Growth explained with Growth ratio does not significantly influence with a negative direction on dividend policy, and (3) Solvability as explained by Debt to Equity Ratio has a significant effect with a negative direction on dividend policy.Implications- The practical implications of the results of this study for managerial policy makers as dividends are expected to maintain and improve the company's financial performance and overall performance every period. This is simply so that the company can still be a profitable company, and be able to provide dividends that are expected by shareholdersKeywords: Profitability, Assets Growth, Leverage, and Dividend Policies